Effects of pulmonary rehabilitation combined with inspiratory muscle training on lung function and exercise capacity in older patients with COPD: a systematic review and meta-analysis - Xie, Jun; Zhu, Yang; Wang, Ya; Mo, Yunjun; Shi, Xiaohui; Liang, Wen-Ming; Ren, Fei-Fei; Bai, Zhenmin; Nie, Feng (Frontiers in Medicine, 2025)
BackgroundPulmonary rehabilitation is central to COPD management, with inspiratory muscle training (IMT) as a key component. However, evidence is inconsistent on whether combining PR with IMT offers added benefits for older COPD patients.ObjectiveTo evaluate the comparative effects of PR combined with IMT versus PR alone on key outcomes in older COPD patients, including quality of life [St. George’s Respiratory Questionnaire (SGRQ)], exercise tolerance [6-min walk distance (6MWD)], respiratory muscle strength [maximal inspiratory pressure (PImax)], and pulmonary function metrics (FEV1, FEV1%).MethodsA systematic search of PubMed, EMBASE, Web of Science, and the Cochrane Library (January 2005–January 2025) identified randomized controlled trials (RCTs) meeting criteria: (1) participants were ≥ 55 years old with GOLD stage II–IV COPD; (2) interventions compared PR combined with IMT versus PR alone; (3) outcomes included PImax, FEV1, FEV1%, SGRQ, and 6MWD. Non-English and animal studies were excluded. Risk of bias was assessed using Cochrane RoB 2.0, and the certainty of evidence was evaluated via the GRADEpro 3.6.1.ResultsNine RCTs (582 patients) were included. Compared with PR alone, PR combined with IMT did not improve 6MWD (SMD = 0.15, 95% CI: −0.11–0.42; low-quality evidence) or SGRQ scores (SMD = −0.19, 95% CI: −0.38–0.01, low-quality evidence). PImax improved moderately (SMD = 0.78, 95% CI: 0.44–1.13, I2 = 48.7%, low-quality evidence). FEV1 and FEV1% trended upward (SMD = 0.50 and 0.58, respectively) but showed high heterogeneity (FEV1: I2 = 72.9%, p = 0.025, very low-quality evidence; FEV1%: I2 = 75.6%, p = 0.006, low-quality evidence), precluding significance. Subgroup analyses showed significant PImax improvements in interventions lasting ≥ 12 weeks (SMD = 0.866, 95% CI: 0.579–1.153; I2 = 0%) or with weekly cumulative durations ≥ 180 min (SMD = 0.922, 95% CI: 0.666–1.177; I2 = 0%), with no 6MWD benefits in any subgroup.ConclusionLow-quality evidence indicates that PR combined with IMT improves respiratory muscle strength (PImax) in older COPD patients versus PR alone, with no significant benefit for exercise capacity (6MWD) or lung function. For older COPD patients, ≥ 12-week PR combined with IMT interventions (sessions > 60 min; weekly duration ≥ 180 min) may enhance PImax.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251010168, CRD420251010168.